"Death was not in the agenda for the day": Emotions, behavioral reactions, and perceptions in response to the 2018 Hawaii Wireless Emergency Alert. (May 2019) - DeYoung, Sarah E.; Sutton, Jeannette N.; Farmer, Ashley K.; Neal, David; Nichols, Katherine A.
Abstract: This research has three main aims: to identify perceptions about the false alarm ballistic missile warning that occurred in Hawaii (United States) in January of 2018, to identify what kind of behavior or actions people took upon receiving the warning, and to identify what situational or contextual factors are related to these perceptions and behaviors. We use a mixed-methods approach to address these research aims. We recruited respondents through social media and email networks (volunteer sampling) to complete a survey that contained categorical and open-ended questions about information gathering, perceptions of self and others during the event, demographic information, and thoughts about trust in future warnings. Using content analysis coding, four main themes emerged from the responses: emotional reactions, protective action, vulnerability and situational factors, and statements about information and trust. Participants sought additional information and cues about the potential threat, observed others engaging in milling, and some accounts of fatalism (during the event) and lingering symptoms associated with traumatic stress (after the event). These findings may be useful for emergency managers and planners designing future warning messaging systems.